Question
upstudy study bank question image url

Write the standard form of the equation and the general form of the equation of the circle with radius \( r \) and center \( (h, k) \). Then graph the circle. \( r=5 ; \quad(h, k)=(-4,-3) \) The standard form of the equation of this circle is \( (x+4)^{2}+(y+3)^{2}=25 \). The general form of the equation of this circle is (Simplify your answer.)

Ask by Carroll Schwartz. in the United States
Feb 26,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

The general form of the equation is \( x^{2} + y^{2} + 8x + 6y = 0 \).

Solution

We start with the standard form of a circle with center (h, k) and radius r:   (x – h)² + (y – k)² = r² Given h = –4, k = –3, and r = 5, the standard form becomes   (x + 4)² + (y + 3)² = 25 To express this in the general form, we expand and simplify the equation: 1. Expand (x + 4)² and (y + 3)²:   (x + 4)² = x² + 8x + 16   (y + 3)² = y² + 6y + 9 2. Combine the expansions:   x² + 8x + 16 + y² + 6y + 9 = 25 3. Combine like terms (16 + 9 = 25):   x² + y² + 8x + 6y + 25 = 25 4. Subtract 25 from both sides to write in general form:   x² + y² + 8x + 6y = 0 So, the general form of the equation is:   x² + y² + 8x + 6y = 0 Graphing the Circle: • Center: (–4, –3) • Radius: 5 Key points on the circle can be found by moving 5 units in the cardinal directions from the center:   – Rightmost point: (–4 + 5, –3) = (1, –3)   – Leftmost point: (–4 – 5, –3) = (–9, –3)   – Topmost point: (–4, –3 + 5) = (–4, 2)   – Bottommost point: (–4, –3 – 5) = (–4, –8) To sketch the graph:  1. Plot the center at (–4, –3).  2. Plot the four key points listed above.  3. Draw a smooth curve passing through these points to form the circle. This completes the answer: Standard form: (x + 4)² + (y + 3)² = 25 General form: x² + y² + 8x + 6y = 0

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

The Deep Dive

To convert the standard form \( (x + 4)^{2} + (y + 3)^{2} = 25 \) into general form, you'll want to expand the equation: 1. Expand each square: \( (x + 4)^{2} = x^{2} + 8x + 16 \) \( (y + 3)^{2} = y^{2} + 6y + 9 \) 2. Combine them: \( x^{2} + 8x + 16 + y^{2} + 6y + 9 = 25 \) 3. Move \( 25 \) to the left side: \( x^{2} + 8x + y^{2} + 6y + 16 + 9 - 25 = 0 \) 4. Simplify: \( x^{2} + 8x + y^{2} + 6y = 0 \) Thus, the general form of the equation of the circle is: \( x^{2} + 8x + y^{2} + 6y = 0 \) --- Drawing the circle based on the equation: To graph this circle centered at \((-4, -3)\) with a radius of \(5\), start by plotting the center. From the center, move \(5\) units in all four cardinal directions: up, down, left, and right. Connect these points in a round shape to visualize the complete circle!

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy